Production of laccase by Resinicium bicolor in submerged cultures: application of the Plackett-Burman experimental design to screen major factors - Shah , Harmen; Yusof, Faridah; Alam, Md. Zahangir (2014)
The present work was aimed towards the evaluation of effects of the physical and chemical factors on laccase production by white rot fungus, Resinicium bicolor ATCC 64897 under submerged condition in shake flask using PlackettBurman design. R.bicolor potentially detoxifies ground tire rubber (GTR) and facilitates growth of Thiobacillus ferrooxidans, a bacterium that performs devulcanization of GTR but is sensitive towards rubber additives present in GTR. In this experiment out of 11 factors screened, copper sulphate and yellow flame bark powder were found to be the most significant factors affecting the laccase production. The study indicated that the screened factors can be optimized for enhanced laccase production and can potentially be utilized for attaining maximum detoxification of GTR and hence further devulcanization.